English language proficiency, health literacy, and trust in physician are associated with shared decision making in rheumatoid arthritis - Barton, Jennifer L; Trupin, Laura; Tonner, Chris; Imboden, John; Katz, Patricia; Schillinger, Dean; Yelin, Edward (Journal of rheumatology, 2014)
Treat-to-target guidelines promote shared decision making (SDM) in rheumatoid arthritis (RA). Also, because of high cost and potential toxicity of therapies, SDM is central to patient safety. Our objective was to examine patterns of perceived communication around decision making in 2 cohorts of adults with RA. Data were derived from patients enrolled in 1 of 2 longitudinal, observational cohorts [University of California, San Francisco (UCSF) RA Cohort and RA Panel Cohort]. Subjects completed a telephone interview in their preferred language that included a measure of patient-provider communication, including items about decision making. Measures of trust in physician, education, and language proficiency were also asked. Logistic regression was performed to identify correlates of suboptimal SDM communication. Analyses were performed on each sample separately. Of 509 patients across 2 cohorts, 30% and 32% reported suboptimal SDM communication. Low trust in physician was independently associated with suboptimal SDM communication in both cohorts. Older age and limited English proficiency were independently associated with suboptimal SDM in the UCSF RA Cohort, as was limited health literacy in the RA Panel Cohort. This study of over 500 adults with RA from 2 demographically distinct cohorts found that nearly one-third of subjects report suboptimal SDM communication with their clinicians, regardless of cohort. Lower trust in physician was independently associated with suboptimal SDM communication in both cohorts, as was limited English language proficiency and older age in the UCSF RA Cohort and limited health literacy in the RA Panel Cohort. These findings underscore the need to examine the influence of SDM on health outcomes in RA.